Dissipation as a mechanism of energy gain - de Carvalho, R. Egydio [UNESP]; Abud, C. Vieira [UNESP]; Souza, F. Caetano (Amer Physical Soc, 2008)
Some properties of the annular billiard under the presence of weak dissipation are studied. We show, in a dissipative system, that the average energy of a particle acquires higher values than its average energy of the conservative case. The creation of attractors, associated with a chaotic dynamics in the conservative regime, both in appropriated regions of the phase space, constitute a generic mechanism to increase the average energy of dynamical systems.